Adoptive Transfer of mRNA-Transfected T Cells Redirected against Diabetogenic CD8 T Cells Can Prevent Diabetes - Fishman, Sigal (Mol Ther, 2017)
Chimeric major histocompatibility complex (MHC) molecules supplemented with T cell receptor (TCR) signaling motifs function as activation receptors and can redirect gene-modified T cells against pathogenic CD8 T cells. We have shown that β(2) microglobulin (β(2)m) operates as a universal signaling component of MHC-I molecules when fused with the CD3-ζ chain. Linking the H-2K(d)-binding insulin B chain peptide insulin B chain, amino acids 15–23 (InsB(15–23)) to the N terminus of β(2)m/CD3-ζ, redirected polyclonal CD8 T cells against pathogenic CD8 T cells in a peptide-specific manner in the non-obese diabetic (NOD) mouse. Here, we describe mRNA electroporation for delivering peptide/β(2)m/CD3-ζ genes to a reporter T cell line and purified primary mouse CD8 T cells. The peptide/β(2)m/CD3-ζ products paired with endogenous MHC-I chains and transmitted strong activation signals upon MHC-I cross-linking. The reporter T cell line transfected with InsB(15–23)/β(2)m/CD3-ζ mRNA was activated by an InsB(15–23)-H-2K(d)-specific CD8 T cell hybrid only when the transfected T cells expressed H-2K(d). Primary NOD CD8 T cells expressing either InsB(15–23)/β(2)m/CD3-ζ or islet-specific glucose-6-phosphatase catalytic subunit-related protein, amino acids 206–214 (IGRP(206–214))/β(2)m/CD3-ζ killed their respective autoreactive CD8 T cell targets in vitro. Furthermore, transfer of primary CD8 T cells transfected with InsB(15–23)/β(2)m/CD3-ζ mRNA significantly reduced insulitis and protected NOD mice from diabetes. Our results demonstrate that mRNA encoding chimeric MHC-I receptors can redirect effector CD8 against diabetogenic CD8 T cells, offering a new approach for the treatment of type 1 diabetes.